2004
DOI: 10.1016/j.devcel.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Checkpoints in the Regulation of Mitotic Progression

Abstract: Accurate chromosome segregation relies on the precise regulation of mitotic progression. Regulation involves control over the timing of mitosis and a spindle assembly checkpoint that links anaphase onset to the completion of chromosome-microtubule attachment. In this paper, we combine live-cell imaging of HeLa cells and protein depletion by RNA interference to examine the functions of the Mad, Bub, and kinetochore proteins in mitotic timing and checkpoint control. We show that the depletion of any one of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

59
523
7
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 444 publications
(596 citation statements)
references
References 52 publications
59
523
7
7
Order By: Relevance
“…Mutation of Drosophila bub1 [Basu et al, 1999] or deletion of mad2 in mice [Dobles et al, 2000] or C. elegans [Kitagawa and Rose 1999] promotes chromosome mis-segregation and early embryonic lethality. These results suggest that the spindle checkpoint regulates mitotic timing in every cell cycle, an idea that is supported by experiments demonstrating that impaired function of Mad2p or Mad3p/BubR1p accelerates mitotic progression Meraldi et al, 2004a].…”
Section: The Spindle Checkpoint Is Required For Accurate Chromosome Smentioning
confidence: 62%
See 1 more Smart Citation
“…Mutation of Drosophila bub1 [Basu et al, 1999] or deletion of mad2 in mice [Dobles et al, 2000] or C. elegans [Kitagawa and Rose 1999] promotes chromosome mis-segregation and early embryonic lethality. These results suggest that the spindle checkpoint regulates mitotic timing in every cell cycle, an idea that is supported by experiments demonstrating that impaired function of Mad2p or Mad3p/BubR1p accelerates mitotic progression Meraldi et al, 2004a].…”
Section: The Spindle Checkpoint Is Required For Accurate Chromosome Smentioning
confidence: 62%
“…Similarly, human (h) Bub1p and hMad2 mRNA abundance is increased in proliferative tissues [Ouyang et al, 1998;Pangilinan et al, 1997]. The up-regulation of SAC proteins in rapidly dividing tissues may be necessary because of the critical role they play in regulating mitotic timing Meraldi et al, 2004a;Taylor and McKeon 1997].…”
Section: The Spindle Checkpoint Is Required For Accurate Chromosome Smentioning
confidence: 99%
“…Later studies further indicated that the remaining checkpoint kinase Mps1, participated as Mad2 and BubR1 in the timing mechanism (Tighe et al 2008). Interestingly, the dual functions of Mad2 and BubR1 correlated with different protein pools, localized at kinetochores (checkpoint) or in the cytoplasm (timer), respectively (Meraldi et al 2004).…”
Section: A Checkpoint or Timing Mechanism?mentioning
confidence: 99%
“…This indicated that the checkpoint proteins control the timing of cell division Gorbsky et al 1998;Shannon et al 2002;Taylor and McKeon 1997). A more detailed study based on RNAi depletions of all the human Mad and Bub proteins revealed the existence of two different, separable phenotypes: while all the Mad and Bub proteins are necessary for delaying anaphase in the presence of unattached kinetochores, only Mad2 and BubR1 depletion also resulted in a significant acceleration of mitosis when compared to control-depleted cells (Meraldi et al 2004). This suggested that Mad2 and BubR1, in addition to their checkpoint function, also act as mitotic "timers", while the other proteins, Bub1, Bub3, and Mad1, have a pure checkpoint role with regard to mitotic timing.…”
Section: A Checkpoint or Timing Mechanism?mentioning
confidence: 99%
See 1 more Smart Citation